Fnr and ArcA Regulate Lipid A Hydroxylation in Salmonella Enteritidis by Controlling lpxO Expression in Response to Oxygen Availability - Fernández, Paulina A.; Velásquez, Felipe; Garcias-Papayani, Héctor; Amaya, Fernando A.; Ortega, Jaime; Gómez, Sebastián; Santiviago, Carlos A.; Álvarez, Sergio A. (Frontiers in Microbiology, 2018)
Lipid A is the bioactive component of lipopolysaccharide, and presents a dynamic structure that undergoes modifications in response to environmental signals. Many of these structural modifications influence Salmonella virulence. This is the case of lipid A hydroxylation, a modification catalyzed by the dioxygenase LpxO. Although it has been established that oxygen is required for lipid A hydroxylation acting as substrate of LpxO in Salmonella, an additional regulatory role for oxygen in lpxO expression has not been described. The existence of this regulation could be relevant considering that Salmonella faces low oxygen tension during infection. This condition leads to an adaptive response by changing the expression of numerous genes, and transcription factors Fnr and ArcA are major regulators of this process. In this work we describe for the first time that lipid A hydroxylation and lpxO expression are modulated by oxygen availability in Salmonella enterica serovar Enteritidis (S. Enteritidis). Biochemical and genetic analyses indicate that this process is regulated by Fnr and ArcA controlling the expression of lpxO. In addition, according to our results this regulation occurs by direct binding of both transcription factors to specific elements present in the lpxO promoter region. Altogether, our observations revealed a novel role for oxygen acting as an environment signal controlling lipid A hydroxylation in S. Enteritidis.